Floral traits mediate the vulnerability of aloes to pollen theft and inefficient pollination by bees - Hargreaves, Anna L.; Harder, Lawrence D.; Johnson, Steven D. (Annals of botany, 2012)
• Background and Aims Pollen-collecting bees are among the most important pollinators globally, but are also the most common pollen thieves and can significantly reduce plant reproduction. The pollination efficiency of pollen collectors depends on the frequency of their visits to female(-phase) flowers, contact with stigmas and deposition of pollen of sufficient quantity and quality to fertilize ovules. Here we investigate the relative importance of these components, and the hypothesis that floral and inflorescence characteristics mediate the pollination role of pollen collection by bees. • Methods For ten Aloe species that differ extensively in floral and inflorescence traits, we experimentally excluded potential bird pollinators to quantify the contributions of insect visitors to pollen removal, pollen deposition and seed production. We measured corolla width and depth to determine nectar accessibility, and the phenology of anther dehiscence and stigma receptivity to quantify herkogamy and dichogamy. Further, we compiled all published bird-exclusion studies of aloes, and compared insect pollination success with floral morphology. • Key Results Species varied from exclusively insect pollinated, to exclusively bird pollinated but subject to extensive pollen theft by insects. Nectar inaccessibility and strong dichogamy inhibited pollination by pollen-collecting bees by discouraging visits to female-phase (i.e. pollenless) flowers. For species with large inflorescences of pollen-rich flowers, pollen collectors successfully deposited pollen, but of such low quality (probably selfpollen) that they made almost no contribution to seed set. Indeed, considering all published bird-exclusion studies (17 species in total), insect pollination efficiency varied significantly with floral shape. • Conclusions Species-specific floral and inflorescence characteristics, especially nectar accessibility and dichogamy, control the efficiency of pollen-collecting bees as pollinators of aloes.